2022
DOI: 10.1021/acsenergylett.1c02425
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Era of Electrolyte Solvation Structure and Interfacial Model in Batteries

Abstract: Over the past two decades, the solid–electrolyte interphase (SEI) layer that forms on an electrode’s surface has been believed to be pivotal for stabilizing the electrode’s performance in lithium-ion batteries (LIBs). However, more and more researchers currently are realizing that the metal-ion solvation structure (e.g., Li+) in electrolytes and the derived interfacial model (i.e., the desolvation process) can affect the electrode’s performance significantly. Thus, herein we summarize recent research focused o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
216
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 375 publications
(258 citation statements)
references
References 211 publications
6
216
0
Order By: Relevance
“…Schematic diagram of the de‐solvation process 31 . Reproduced with permission: 2022, American Chemical Society 31 …”
Section: Binding Energy Regulationmentioning
confidence: 99%
See 3 more Smart Citations
“…Schematic diagram of the de‐solvation process 31 . Reproduced with permission: 2022, American Chemical Society 31 …”
Section: Binding Energy Regulationmentioning
confidence: 99%
“…Quantum chemistry calculations showed that the binding energies were À5.27 and F I G U R E 7 Schematic diagram of the de-solvation process. 31 Reproduced with permission: 2022, American Chemical Society 31 À1.38 kJ mol À1 when FEC/FEMC and FEC/DEC were at a ratio of 1:3, much lower than EC/DMC (3:1 molar) of À37.86 kJ mol À1 . Their binding energies were further reduced after they were dissolved in high-fluorine solvents.…”
Section: Regulation Of Binding Energy For Low-temperature Batteriesmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 51 ] However, it remains challenging to elucidate the desolvation process of Li ions (as well as other ions), since the process is abstractive, dynamic, and non‐quantitative. [ 52 ] Moreover, the structure of the Li‐ion solvation and the electric double layer determine this dynamic process but could easily be altered if changing either the electrolyte concentration or composition (salts, solvents, and additives). A lack of feasible operando characterization tools further hinders an in‐depth understanding of the Li‐ions dynamics at the electrochemical interface.…”
Section: Mysteries In LI Deposition and Perspectives For Deeper Under...mentioning
confidence: 99%